2014
DOI: 10.1051/0004-6361/201424534
|View full text |Cite
|
Sign up to set email alerts
|

ASTE observations in the 345 GHz window towards the HII region N113 of the Large Magellanic Cloud

Abstract: Aims. The HII region N113 is located in the central part of the Large Magellanic Cloud (LMC) with an associated molecular cloud that is very rich in molecular species. Most of the previously observed molecular lines cover the frequency range 85-270 GHz. Thus, a survey and study of lines at the 345 GHz window is required for a more complete understanding of the chemistry and excitation conditions of this region. Methods. We mapped a region of 2. 5 × 2. 5 centred at N113 using the Atacama Submillimeter Telescope… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 37 publications
2
15
0
Order By: Relevance
“…Herrera et al (2013), using the 12 CO J=2-1, obtained similar relations between M vir and M LTE for most of their catalogued clumps in N11. Our results, obtained with the 13 CO, an optically thinner tracer, show that even deeper parts of the molecular clumps are not gravitationally bounded and may be supported by external pressure, as found in molecular clouds around Galactic Hii regions (Rathborne et al 2002;Massi et al 1997), and in the LMC, in N113 (Paron et al 2014) and Cloud B of Complex No.37 (Garay et al 2002).…”
Section: Discussionsupporting
confidence: 56%
“…Herrera et al (2013), using the 12 CO J=2-1, obtained similar relations between M vir and M LTE for most of their catalogued clumps in N11. Our results, obtained with the 13 CO, an optically thinner tracer, show that even deeper parts of the molecular clumps are not gravitationally bounded and may be supported by external pressure, as found in molecular clouds around Galactic Hii regions (Rathborne et al 2002;Massi et al 1997), and in the LMC, in N113 (Paron et al 2014) and Cloud B of Complex No.37 (Garay et al 2002).…”
Section: Discussionsupporting
confidence: 56%
“…Early studies by the SEST 15 m telescope conducted multiline observations toward H II regions in the LMC and detected molecular species as large as CH 3 OH, C 3 H 2 , and SO 2 (Johansson et al 1994;Chin et al 1997;Heikkilä et al 1999;Wang et al 2009). Submillimeter observations of relatively dense molecular gas in star-forming regions in the LMC are also reported (Paron et al 2014(Paron et al , 2016. Nishimura et al (2016) recently conducted deep and unbiased spectral line surveys in the 3 mm window toward a number of molecular clouds in the LMC using the Mopra telescope.…”
Section: Introductionmentioning
confidence: 99%
“…With the idea of carry out a comparative study of the physical conditions of the molecular gas in Hii regions in the LMC using molecular lines in the 345 GHz windows, we have made observations with the Atacama Submillimetre Figure 1. Main area of the LMC in which the location of the Hii regions studied in this paper (N159, N132, and N166) and N133 from Paron et al (2014) are indicated. As reference, 30 Dor and the location of the LMC molecular ridge are also showed.…”
Section: Introductionmentioning
confidence: 99%